The dragon's child - Nimmo, Jenny; Marks, Alan, 1957- (New York : Orchard Books, 2008)
Dando, a young dragon who cannot fly, is captured by dangerous humans, but a kind slave girl, an orphaned bird, and the melancholy son of the dragon's captor help him escape his imprisonment and learn to fly.
Die-cut pages.
2.7
K-3
K-3
Keywords: Dragons -- Juvenile fiction; Dragons -- Fiction; Dragons -- Fiction